Type of Misconception Genetics Found on Textbook in High School - Elya Nusantari (Universitas Negeri Malang, 2014)
Jenis Miskonsepsi Genetika yang Ditemukan pada Buku Ajar di Sekolah Menengah Atas Abstract: The study aims to reveal the types of misconceptions genetics in high school class XII textbook.  The Textbooks which analyzed is as many as 12 books published in 2007-2010. The analysis was conducted from Mei - October 2010. The research step is to identify the genetic misconceptions page by page and chapter by chapter. The results shows genetic misconceptions found in 7 or entire groups of the concept of the meaning and scope of genetics; genes, DNA and chromosomes; the relationship of genes, RNA, polypeptides, and the process of protein synthesis; linkages between mitotic and meiotic process by inheritance; principles and mechanisms of heredity inheritance; sex determination; and mutations. This is affected with the presentation of information used is the historial version, and classical genetic material still less representative (molecular). Presentation of the concept of genetics does not connect between concepts so that students' understanding  is fragmented. Teachers need to make a selection according to the standard textbook content of the material. Keywords: misconceptions, genetics, high school textbooks, the selection of books Abstrak: Penelitian  bertujuan  mengungkap jenis miskonsepsi   genetika pada buku ajar SMA kelas XII. Buku ajar dianalisis sebanyak 12 buku tahun terbit  2007-2010. Analisis dilakukan mulai Mei-Oktober 2010. Langkah penelitian adalah mengidentifikasi miskonsepsi genetika  halaman demi hala-man dan bab demi bab. Hasil penelitian menunjukkan miskonsepsi genetika ditemukan pada 7 atau seluruh kelompok konsep yakni arti dan ruang lingkup genetika; gen, DNA dan kromosom; hubung-an gen, RNA, polipeptida, dan proses sintesis protein; keterkaitan antara proses pembelahan mitosis dan meiosis dengan pewarisan sifat; prinsip hereditas dan mekanisme pewarisan sifat; penentuan je-nis kelamin; dan mutasi. Hal ini akibat penyajian informasi masih versi sejarah, materi masih genetika klasik dan kurang representatif (molekuler). Penyajian konsep genetika tidak menghubungkan antar konsep sehingga pemahaman siswa terfragmentasi. Guru perlu melakukan seleksi buku ajar sesuai standar isi materi.  Kata kunci: miskonsepsi, genetika, buku ajar SMA, seleksi buku